▪Answer: Option D!
Explanation:
Given:
- y = x +7
- [tex]y = {x}^{2} + 2x + 7[/tex]
Solution :
Substitute y=x + 7 in the second equation!
[tex]y = {x}^{2} + 2x + 7[/tex]
[tex] \implies \: x + 7 = {x}^{2} + 2x + 7[/tex]
[tex] \implies \: {x}^{2} + 2x + 7 - x - 7 = 0[/tex]
[tex] \implies \: {x}^{2} + x = 0[/tex]
[tex] \implies \: x(x + 1) = 0[/tex]
[tex] \implies \: x = 0 \: or \: x = - 1[/tex]
Now put x = 0 in equation 1,
y = x +7
=> y = 0+7
=> y = 7
Now put x=-1 in equation 1,
y = x+7
=> y = -1+7
=> y = 6
The solutions are :
Option D!